Host-targeting therapies for hepatitis C virus infection: current developments and future applications. (21st March 2018) - Crouchet, Emilie; Wrensch, Florian; Schuster, Catherine; Zeisel, Mirjam B.; Baumert, Thomas F.
Chronic hepatitis C virus (HCV) infection is a leading cause of chronic liver diseases and hepatocellular carcinoma (HCC) worldwide. In the past few years, anti-HCV therapies have undergone a revolution with the approval of multiple direct-acting antivirals (DAAs), which enable interferon-free treatments with considerable improvement of sustained virologic response in patients. Today, DAAs have become the standard of care for HCV therapy. However, several limitations remain, which include access to therapy, treatment failure in a subset of patients and persistent risk of HCC development following cure in patients with advanced fibrosis. By targeting conserved host proteins involved in the HCV life cycle, host-targeting agents (HTAs) offer opportunities for pan-genotypic antiviral approaches with a high barrier to drug resistance. Moreover, when applied in combination with DAAs, HTAs could improve the management of difficult-to-treat patients by acting through a complementary mechanism of action. In this review, we summarize the different HTAs evaluated in preclinical and clinical development and discuss their potential role for anti-HCV therapies.